Constraints on universal health care in the Russian Federation: Inequality, informality and the failures of mandatory health insurance reforms - Linda Cook (United Nations Research Institute for Social Development (UNRISD), 2015)
Healthcare in Russia has gone through many transformative stages, from a Soviet-era model of public provision to an emphasis on privatization under economic liberalization during the 1990s. Both have legacies that survive to the present, and now a mix of both public and private healthcare provision operates across Russia. Throughout all these periods, universalism has been enshrined as a guarantee, at least nominally. The extent to which this right has been upheld varies greatly, with some major constraints to universal provision in Russia. Underfinancing presents a persistent obstacle to universal access, and substantial inequalities in healthcare access and quality exist across different regions and income groups, with some vulnerable and marginalized groups left almost entirely excluded. Furthermore, despite efforts to improve quality and provision of healthcare, Russia has a poor record in many health indicators, and its national system is struggling to become more efficient and effective.
Keywords: 330